Preseason Vestibular Ocular Motor Screening in Children and Adolescents. Issue 4 (July 2021) - Iverson, Grant L.; Cook, Nathan E.; Howell, David R.; Collings, Laurel J.; Kusch, Cody; Sun, Jonathan; Virji-Babul, Naznin; Panenka, William J.
Abstract : Objectives: The primary purpose of this study was to examine vestibular/ocular motor screening (VOMS) test performance in a sample of healthy youth ice hockey players. A particular focus was to investigate the potential effects of age and pre-existing health conditions, including concussion history, attention-deficit/hyperactivity disorder (ADHD), learning disability (LD), headaches/migraines, and depression/anxiety on preseason baseline VOMS performance, including the near point of convergence (NPC) distance. Design: Cross-sectional cohort. Setting: Outpatient physiotherapy clinic. Participants: Three hundred eighty-seven male youth hockey players, with an average age of 11.9 years (SD = 2.2, range = 8-17), completed the VOMS and responded to self- or parent-reported demographic and medical history questionnaires during preseason baseline assessments. Independent Variables Assessed: Age, sex, and mental and physical health history including ADHD, headaches, depression, anxiety, migraine, and LD. Outcome Measure: Vestibular/ocular motor screening. Results: The large majority of boys scored within normal limits on the VOMS, ie, they reported no symptom provocation of more than 2 points on any VOMS subset (89%) and had a normal NPC distance, ie, <5 cm (78%). The individual VOMS subtests had low abnormality rates, and demographic and pre-existing health conditions, such as age, headache or migraine history, previous neurodevelopmental conditions, or mental health problems, were not associated with clinically meaningful symptom provocation during the VOMS. Conclusions: There was a low rate of abnormal findings for the individual VOMS subtests, with the exception of NPC distance, among male youth hockey players during preseason assessment.